PENGARUH KAPASITAS OPERASI, PERTUMBUHAN PENJUALAN, KOMISARIS INDEPENDEN, DAN KEPEMILIKAN PUBLIK TERHADAP FINANCIAL DISTRESS - Teti Rahmawati (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
This study aim to examine the effect of the ratio likuiditas, leverage,operating capacity, sales growth, audit committee size, independentcommissioner and public ownership on financial distress.The population ofthis study is manufacture company listed on the Indonesia Stock Exchangefor period of 2009-2015. Based on purposive sampling method, this sampleof this study are 281 companies (159 financial distress and 122 nonfinancial distress). The criteria is used to categorize a financial distresscompany in this study based on earning per share (EPS) negative. Dataanalysis using regression logistic.The result show that the sales growth,operating capacity, independent commissioner and public ownership have asignificant on financial distress.